Prehistoric worlds - Hall, Ashley, (Paleontologist); McElfatrick, Claire (London : Dorling Kindersley Limited, 2024)
Plants flourish, birds evolve, and dinosaurs charge across the pages of this lively and colourful book. Packed with dynamic historical content, it combines stunning illustrations and photos to help young historians learn all about the period that shaped our planet. From oceans teeming with life to destructive asteroids, they'll discover the incredible timeline of life that resulted in the world we recognise today. Meet favourite dinosaurs, from the terrifying T.Rex to the spiky stegosaurus; nurture your inner palaeontologist by learning about prehistoric plant and animal fossils; and discover destructive extinction events that changed the world forever. The Prehistoric Worlds takes children on a fascinating journey through history, showing them how and where their favourite dinosaurs came to exist, and how events from billions of years ago are still affecting our natural world today.
Includes index.
Keywords: Extinct animals -- Juvenile literature; Dinosaurs -- Juvenile literature; Animals, Fossil -- Juvenile literature; Dinosaurs -- Identification -- Juvenile literature; Fossils -- Juvenile literature; Paleontology -- Juvenile literature